PENGARUH KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN LAWEYAN KOTA SURAKARTA - Sudarman, Alwi Suddin & (Universitas Slamet Riyadi, 2010)
ABSTRACT This research aimed: 1) to analyze significant influence of leadership, motivation, and environment partially toward the official’s performance of Laweyan of Surakarta 2) to analyze significant influence of leadership, motivation, and environment simultaneously toward the official’s performance of Laweyan of Surakarta 3) to analyze the dominant variable of leadership, motivation, and environment toward the official’s performance of Laweyan of Surakarta. Population of this research is all the officials of Laweyan Surakarta as 33 officials. Because of the population is less than 100, therefore the entire population become sample in this research. Instrument used is questionnaire. Data analysis uses doubled linier regression, t test, F test, and R2 test. From result analyze data found the quotation of doubled linier regression as follows: Y = 3,659 + 0,487 X1 + 0,272 X2 + 0,600 X3. Leadership variable (X1) influences officials performance, from t account can be known the significant value is as 0,008 < 0, 05. Motivation variable (X2) influences officials performance from t account can be known the significant value is as 0,017 < 0, 05. Environment variable (X3) influences officials performance from t account can be known the significant value is as 0,001 < 0, 05. Because the significance value is less than 0,05, it can be concluded that there is significant influence of leadership, motivation and environment toward the official performance. The determination coefficient is as 0,744, means that the contribution of leadership, motivation and environment toward the official’s performance of Laweyan of Surakarta is influenced as 74,4% while another as 25,6% is influenced by another factor that is not included in the research. Environment variable influences dominantly toward official’s performance. Keywords: leadership, motivation, environment official’s performance